The Importance of Painting in Qajar Dynasty Based on the Sociology Point of View - Pedram, Behnam; Hosseini, Mahdi; Rahmani, Gholam Reza (Journal of History Culture and Art Research, 2017)
The paintings of Qajar dynasty are the most thriving and important artworks in Qajar dynasty. Studying Qajar painting helps importantly to identify and study the art and culture of Qajar dynasty. Existence of lots of paintings, diversity of designs, color and subject, combining tradition and modernism were factors for selecting this dynasty to investigate. As the painting is the visual history of each era, sociology studying of painting in this dynasty will make one to understand common culture and thinking of people in that society. Amount of influence of western culture especially during Naser al-Din Shah Era has been at the same time with the creation of these paintings and combination of these paintings with our past legacy schools lead us to the thinking and willing of Qajar artists. As Qajar art and different kinds of painting art were the foundation of contemporary Iran’s painting by a research around this Dynasty, the reasons of excellence, lacks and origins of contemporary painting of Iran can be understood. Research methodology at the beginning was based on library studies while there were little reading resources in books, magazines, internet, documentation, presence in places and photography and then studying of what was seen heard and read.